PENGARUH IDEOLOGI TERHADAP SIKAP RADIKAL PIMPINAN PONDOK PESANTREN DI TASIKMALAYA - Moh. Dulkiah (GoAcademica Research dan Publishing, 2020)
Religious understanding is often with people and people using key words. The religious view of the teacher, the interpretation, and the context that surrounds it. Therefore, understanding can produce results from many literal and loud individuals or groups in understanding religion in a social, political, and religious context. This study aims to determine the ideology for the radical attitude of pesantren in Tasikmalaya. The result of this research concludes that the ideology factor has significant effect on radicalism aligned by the leadership of pesantren in Tasikmalaya. Ideological factors against radicalism in the leader of pesantren leaders in Tasikmalaya by 32% are being released by 68% by other variables not examined in this study such as economy, education, revenge and others.